2015
DOI: 10.1111/crj.12419
|View full text |Cite
|
Sign up to set email alerts
|

Office spirometry correlates with laboratory spirometry in patients with symptomatic asthma and COPD

Abstract: In patients with known asthma and chronic obstructive pulmonary disease (COPD), OS is accurate and reliable when compared to formal laboratory-based spirometry. Routine use of OS should be encouraged to improve spirometry utilization and healthcare outcomes in patients with Asthma and COPD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 31 publications
0
12
0
Order By: Relevance
“…Clinically, MIP is the most common technique in the assessment of inspiratory muscle strength, and MEP is the only test generally available for measuring expiratory muscle strength [ 20 ]. The portable spirometer used in this study is accurate and reliable when compared to formal laboratory-based spirometry [ 23 ]. The results, however, are highly dependent on subject motivation, and there might be leaks around the mouth during the performance, especially at higher pressures and in older subjects [ 20 ].…”
Section: Methodsmentioning
confidence: 99%
“…Clinically, MIP is the most common technique in the assessment of inspiratory muscle strength, and MEP is the only test generally available for measuring expiratory muscle strength [ 20 ]. The portable spirometer used in this study is accurate and reliable when compared to formal laboratory-based spirometry [ 23 ]. The results, however, are highly dependent on subject motivation, and there might be leaks around the mouth during the performance, especially at higher pressures and in older subjects [ 20 ].…”
Section: Methodsmentioning
confidence: 99%
“…In Western countries, the portable spirometer has demonstrated consistency that is similar to that of traditional pulmonary function equipment in the determination of various parameters. [9][10][11][12][13] However, scant evidence exists in relation to the reliability of portable spirometry for evaluation of Chinese patients. 14 In this study, we sought to validate the agreement of measurements obtained with portable versus traditional spirometers in a Chinese cohort.…”
Section: Introductionmentioning
confidence: 99%
“…high-risk patients. Although the previous study had shown significant correlation between OS and LS for both forced FEV1 and FVC in patients with COPD (20), it should be also noted that there are patients at high-risk for pulmonary complications even if the spirometry data does not show low FEV1/FVC (8,23). Moreover, it is also great interests of pulmonary physicians whether both FEV1 and FVC of OS show significant association with those of LS in patients with a variety of pathologies.…”
Section: Preoperative Pulmonary Function Testing and Postoperative Comentioning
confidence: 91%
“…For these reasons, some researchers have investigated potential clinical relevance of office-based spirometry (OS) that can be easily performed in outpatient office with less cost and time (19). Previous investigations demonstrated that OS parameters including expiratory volume in one second (FEV1) and forced vital capacity (FVC) had been significantly correlated with LS parameters (20) and OS was reportedly useful for screening of chronic obstructive pulmonary disease (COPD) (21). In a recent paper of Hudson et al in the Annals of Thoracic Surgery (22), the authors demonstrated that patients who had undergone preoperative OS had experienced similar major morbidity to those who had undergone preoperative LS after propensity score matching.…”
mentioning
confidence: 99%